Analysis of Default in Sharia Economic Law Disputes: A Review of The Principles of Justice and Good Faith in Contracts - Akbar Muhamad Ashoni; Mia Amanatul Fitriyah; Oyo Sunaryo Mukhlas (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2026)
This research focuses on the analysis of defaults in sharia economic law disputes, by highlighting aspects of justice and good faith in contracts. In the sharia economy, the application of the principles of justice and good faith is the main basis in guaranteeing the rights and obligations of the parties and resolving disputes fairly in accordance with sharia values. This research uses a juridical normative approach and case studies. Primary data is in the form of court decisions related to defaults in sharia contracts, while secondary data includes laws and regulations (KHES, Civil Code), DSN-MUI fatwas, and academic literature. The analysis was carried out descriptively and comparatively based on the principles of justice and good faith in positive law and sharia law. The results of the study show that the application of the principles of justice and good faith shows a significant influence on the resolution of default disputes. The application of sharia values in the practice of banking and Islamic financial institutions is able to uphold justice, avoid unjust actions, and ensure balanced treatment for all parties. The discussion emphasized that the implementation of the values of justice and good faith in contracts and dispute resolution must be carried out consistently and comprehensively. The application of these principles is important to maintain the harmony of sharia law and values in sharia economic practices, so that its sustainability and justice can be guaranteed.